Pengembangan Media Pembelajaran Berbasis Aplikasi Canva dengan Model Microblogging sebagai Pembelajaran Teks Prosedur Tingkat SMP - Muhammad Aditya Wisnu Wardana; Adina Anisnaeni Rizqina; Adzkiyah Nur Salsabilah; Desyntia Amanda Putri Handayani; Safira Meisa Dewi; Chafit Ulya (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to develop Canva-based learning media with a renewable model with Microblogging which is used as a procedure text language learning at the junior high school level. The development of Canva-based learning media with the Microblogging model is carried out in 4 stages, namely (1) the define stage; (2) the design stage (design); (3) the development stage and the disseminate stage. This research was conducted by taking samples from educators and students in grades VII A and VII B of SMP Negeri 1 Wlingi by asking questions to one of the language educators through the media zoom meeting and students go through the google form to find out what kind of learning media has been used by educators at the school. It is hoped that with the development of the Canva application with the Microblogging model, it is able to provide solutions to the conventional teaching and learning process of teachers to turn it into learning that is in harmony with the development of technology and information so that students are able to be more interactive and active in paying attention to and receiving the learning material presented by the teacher.